2017
DOI: 10.3329/ajmbr.v2i4.30992
|View full text |Cite
|
Sign up to set email alerts
|

Cycloartenyl Ferulate downregulates lipopolysaccharide stimulated iNOS mRNA via NF-kB suppression in RAW 264.7 macrophages

Abstract: Cycloartenyl ferulate (CAF) is a major bioactive phytosteryl ferulate purified from rice bran γ-oryzanol. Previously we reported that CAF ameliorates DSS-induced colitis in mice. The present study was undertaken to investigate the effects of CAF on LPS (lipopolysaccharide) stimulated murine RAW 264.7 macrophages. Immunohistochemistry analysis demonstrated that LPS (10ng/mL) treatment exhibited nuclear translocation of NF-B-p65 in RAW macrophages, which was markedly inhibited CAF (30M). LPS (10ng/mL) stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…As shown in Fig 1A and 1B, secretion of the inflammatory cytokines IL-6 and TNF-α was significantly suppressed by RBO treatment, while secretion of the anti-inflammatory cytokine IL-10 was reciprocally upregulated (Fig 1F). In this regard, Islam et al also reported that cycloartenyl ferulate extracted from rice bran downregulated the transcription of iNOS mRNA in an NF-kB-dependent manner in LPS-stimulated RAW 264.7 macrophages [30]. In contrast, Sierra et al reported that RBO enhanced the production of Th1-prone cytokines (i.e., IL-2 and TNF-α) and the proliferation of B cells in splenocytes compared to high-oleic sunflower oil [31].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Fig 1A and 1B, secretion of the inflammatory cytokines IL-6 and TNF-α was significantly suppressed by RBO treatment, while secretion of the anti-inflammatory cytokine IL-10 was reciprocally upregulated (Fig 1F). In this regard, Islam et al also reported that cycloartenyl ferulate extracted from rice bran downregulated the transcription of iNOS mRNA in an NF-kB-dependent manner in LPS-stimulated RAW 264.7 macrophages [30]. In contrast, Sierra et al reported that RBO enhanced the production of Th1-prone cytokines (i.e., IL-2 and TNF-α) and the proliferation of B cells in splenocytes compared to high-oleic sunflower oil [31].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that LPS, as a toxin that induces oxidative damage, has been widely used to establish animal models of inflammation and bacterial infections. LPS activates the NF-κB signaling pathway through toll-like receptor (TLR-4), and promotes the production of downstream inflammatory cytokines including IL-1β, IL-6, TNF-α [6]. It is reported that cell SOD activity was decreased, the level of oxidative stress was increased and cell activity was reduced in LPS treated pheochromocytoma murine adrenoma cell (PC12).…”
Section: Introductionmentioning
confidence: 99%